Reorienting Cash Waqf for Economic Development: A Maqāşid Sharia Perspective Study on the Indonesian Waqf Board (BWI) Case in Parepare - Arwin; Faiz, Abd. Karim (Universitas Islam Negeri Alauddin Makassar, 2023)
Cash waqf, an initiative introduced by BWI Parepare City, initially aimed to alleviate post-Covid-19 poverty in the region. However, its implementation has proven ineffective and counterproductive to local economic development. In order to gain a comprehensive understanding of the issue, a qualitative study was conducted, consisting of interviews at the BWI Office and PCNU in Parepare City, to gather relevant data. The study aimed to provide a description of currency waqf from both a fiqh and positive law perspective, while also conducting a Maqāşid Sharia-centric analysis of the reorientation of cash waqf at BWI Parepare City. The first finding showed that cash waqf involved depositing funds in financial institutions for socioreligious purposes. However, the second finding indicated the issue with the current cash waqf implementation in Parepare City, as it lacked orientation and failed to contribute effectively to economic development. This study discusses the implications of cash waqf in facilitating economic recovery, emphasizing the need for waqf fiqh to align with concepts that genuinely benefit the people and remain adaptable to the prevailing conditions. The aim is to ensure the implementation of cash waqf in a manner that supports economic development and maintains harmony with the present circumstances